THERAPEUTIC SIGNIFICANCE OF FENUGREEK W.S.R TO ITS HYPOLIPIDEMIC ACTIVITY - Meenakshi, *Pandey; D.C, Singh; Naveen, Kumar; Asheesh, Kandpal (International Journal of Ayurveda and Pharma Research, 2017)
The term Hyperlipidemia denotes excessive cholesterol in the blood. It is both LDL and triglycerides that are elevated in hyperlipidemia. As per Ayurveda, In Hyperlipidemia, Medodhatu vitiates because of improper working of Parthiva and Aapbhutagni rasa and Medodhatvagni. Mainly Asthivahasrotas are affected. Asthivahasrotas build from Medo and Jaghan part. Fenugreek having lipolytic property and it primarily works on Annahvahasrotas and Asthivahasrotas. It decreases cholesterol level, reduces body weight by decreasing plasma triglycerides and having hepatoprotective effect. Fenugreek (Trigonella foenum graecum) commonly known as Methi, family Fabaceae is a annual plant, cultivated world wide as a semiarid crop. The seeds of fenugreek are used as condiment and dried leaves as flavouring agent. Vegetative parts are rich in vit A, vit B and iron. Constituents of fenugreek seeds include flavonoids, alkaloids, coumarins, saponins; most prevalent alkaloid is trigonelline and coumarins include cinnamic acid and scopoletin. In southern part of india roasted seeds in the form of infusion are indicated in diarrhoea and small pox. It is an appetizer and carminative. Its porridge is used as galactagogue. Having antidiabetic, antiallergic, lactation induced, anti-oxidant potency. In this article we are going to discuss about fenugreek in all aspects including its Anti-hyperlipidemic action.